REPRESENTASI PATRIARKI PADA TOKOH UTAMA DALAM SERIAL GADIS KRETEK KAJIAN SEMIOTIKA JOHN FISKE - Zafira Ardhea Rista; Anisha Intan Prameswari; Vania Abigail Putri Andrias (Sintesa, 2026)
Film series have developed so rapidly among the public. In addition to being entertaining, serial films have the power to change society, affecting everything from people's ways of thinking to their daily behavior. This study analyzes the representation of patriarchy in the main characters of the "Gadis Kretek" series using John Fiske's semiotic approach. This series, adapted from Ratih Kumala's novel, presents a powerful narrative about women's experiences within the patriarchal structure of Javanese society in the 1960s. Using a qualitative descriptive method, this study examines Fiske's three levels of semiotic codes: the level of reality (social codes), the level of representation (technical codes), and the level of ideology. Data was obtained thru visual observation, scene analysis, and dialog documentation from the series. The research findings indicate that the character of Dasiyah represents the subordination of women within the patriarchal system thru limited access to the production sphere, unfair recognition of achievements, and restricted social mobility. However, the series also showcases symbolic forms of resistance thru Dasiyah's courage in rejecting arranged marriage, pursuing her passion in a male-dominated field, and maintaining her skills despite lacking public recognition. Comparison with the male character Soeraja reveals the patriarchal dominance that allows for broader social mobility and autonomy in decision-making. This research contributes to understanding how audio visual media represents and critiques patriarchal structures thru narrative, cinematic techniques, and character development. Keywords : Serial Film, Semiotics, Patriarchy, Feminism, John Fiske, Gender Representation